2010
DOI: 10.1080/10508610903418129
|View full text |Cite
|
Sign up to set email alerts
|

Specific Religious Beliefs in a Cognitive Appraisal Model of Stress and Coping

Abstract: Although religiousness is tied to coping, little work examines the role of specific religious beliefs in the coping process. Applying the transactional model of coping, positivity of God image and vertical religious focus were assessed in a national sample of 103 parents of children with disabilities. Controlling for general religiousness, these specific beliefs were correlated with parents' appraisals. Positive God image was associated positively with appraisals that the disability is a challenge, a benefit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 37 publications
(48 reference statements)
5
34
0
7
Order By: Relevance
“…Finally, sample differences may influence the results. As reported elsewhere (Newton and McIntosh , ; Park, Cohen, and Herb ) and theorized here, individual differences in religion can influence psychological responses; differences in religious beliefs between a sample from Texas and one from the western United States may alter outcomes. Future work should investigate these possibilities, as well as explore more generally factors that can integrate and explain the varying findings from religious priming studies.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Finally, sample differences may influence the results. As reported elsewhere (Newton and McIntosh , ; Park, Cohen, and Herb ) and theorized here, individual differences in religion can influence psychological responses; differences in religious beliefs between a sample from Texas and one from the western United States may alter outcomes. Future work should investigate these possibilities, as well as explore more generally factors that can integrate and explain the varying findings from religious priming studies.…”
Section: Discussionsupporting
confidence: 62%
“…Correlational studies of religion's influence are consistent with the idea that religion confers existential security (Baker and Gorsuch ; Beck ; Hood et al ; Hui, Bond, and Ng ; Norenzayan et al ) and that the effects of religious beliefs (e.g., religious coping appraisals, intrinsic orientation) differ depending on a person's faith tradition or religious denomination (Newton and McIntosh , ; Park, Cohen, and Herb ). A recent investigation specific to existential functions revealed that defensive religion (i.e., beliefs that are simplistic, dogmatic, and provide certainty) provides meaning in life through the promise of literal immortality and enhanced religious commitment (Van Tongeren, Hook, and Davis forthcoming), suggesting that the type of religious beliefs one endorses has important implications for existential security.…”
Section: The Existential Function Of Religionmentioning
confidence: 58%
See 1 more Smart Citation
“…Hill and Hall (2002) had established the effect of elements such as family, society, interactions with people and religious learning/activities on a person's understanding of God. Newton and McIntosh (2010), in their works on the impact of the parents' perception of God on their empathetic potential, discovered that people with positive perceptions of God have enhanced capacities for psychological comforting and that they face challenges more positively. People, who have experienced warm and supportive relationship with their parents have higher self-esteem and believe God to be kind, giving and caring-wherein they develop a perception of God as a loving God, and a spirituality that is founded more on the "love of God" as opposed to "the fear of God".…”
Section: Introductionmentioning
confidence: 99%
“…It has been emphasized that violence in the family can be a constant source of stress for runaway children. With such violent and abusive family backgrounds, these children are more likely to perceive stressors as uncontrollable and coping as impossible (Newton & McIntosh, 2010). It must also be kept in mind that for successful coping with stressors, a supportive family is considered to be an anchor for children.…”
mentioning
confidence: 99%